2013
DOI: 10.1200/jco.2012.44.5643
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Multicenter, Open-Label Study of Oxaliplatin Plus Fluorouracil/Leucovorin Versus Doxorubicin As Palliative Chemotherapy in Patients With Advanced Hepatocellular Carcinoma From Asia

Abstract: Although the study did not meet its primary end point, the trend toward improved OS with FOLFOX4, along with increased PFS and RR, suggests that this regimen may confer some benefit to Asian patients, but an OS benefit cannot be concluded from these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
352
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(374 citation statements)
references
References 29 publications
15
352
4
3
Order By: Relevance
“…In a randomized phase III study, FOLFOX showed improved ORR (8.2% vs. 2.7%, P=0.02) and improved PFS (median PFS: 2.9 vs. 1.8 months, P≤0.001) with a non-significant trend for increased OS (median OS: 6.4 vs. 5.0 months, P=0.07) compared with single agent doxorubicin (38). The most common grade 3 to 4 adverse events from FOLFOX were neutropenia (30.6%), leukocytopenia (8.7%), thrombocytopenia (7.7%) and anemia (4.9%) in the study.…”
Section: -Fu Based Combination Chemotherapymentioning
confidence: 99%
“…In a randomized phase III study, FOLFOX showed improved ORR (8.2% vs. 2.7%, P=0.02) and improved PFS (median PFS: 2.9 vs. 1.8 months, P≤0.001) with a non-significant trend for increased OS (median OS: 6.4 vs. 5.0 months, P=0.07) compared with single agent doxorubicin (38). The most common grade 3 to 4 adverse events from FOLFOX were neutropenia (30.6%), leukocytopenia (8.7%), thrombocytopenia (7.7%) and anemia (4.9%) in the study.…”
Section: -Fu Based Combination Chemotherapymentioning
confidence: 99%
“…Grade 3/4 adverse effects were similar in both groups. Although this trial demonstrated improved OS following FOLFOX4 treatment, sorafenib-the current standard of care for advanced HCC-was not used as a comparison, thus limiting the applicability of these findings (46).…”
Section: Cytotoxic Systemic Chemotherapymentioning
confidence: 99%
“…Combination chemotherapy with 5-fluorouracil, leucovorin, and oxaliplatin (FOLFOX4) was compared with doxorubicin monotherapy in an Asian trial (46). Median OS was 6.40 months with FOLFOX4 and 4.97 months with doxorubicin (HR, 0.80; 95% CI, 0.63 to 1.02; P=0.07); median PFS was 2.93 vs. 1.77 months (HR, 0.62; 95% CI, 0.49-0.79; P<0.001).…”
Section: Cytotoxic Systemic Chemotherapymentioning
confidence: 99%
“…The study is based on a multicenter randomized clinical trial, known as the EACH study, conducted from March 2007 to May 2009 [10].The EACH study was carried out in Southeast Asian countries, from which patients with a confirmed diagnosis of advanced HCC were randomized in a 1:1 ratio into one of two chemotherapy regimens, namely, FOLFOX4 (oxaliplatin, leucovorin, 5-fluorouracil) or doxorubicin. The results of the whole EACH study have already been published in full in 2013 [10].…”
mentioning
confidence: 99%
“…The study is based on a multicenter randomized clinical trial, known as the EACH study, conducted from March 2007 to May 2009 [10].The EACH study was carried out in Southeast Asian countries, from which patients with a confirmed diagnosis of advanced HCC were randomized in a 1:1 ratio into one of two chemotherapy regimens, namely, FOLFOX4 (oxaliplatin, leucovorin, 5-fluorouracil) or doxorubicin. The results of the whole EACH study have already been published in full in 2013 [10]. In summary, the study failed to meet its primary objective of improvement in overall survival (6.4 months in the FOLFOX4 arm vs. 5.0 months in the doxorubicin arm; p 5 .07) despite an improvement in progression-free survival favoring the FOLFOX4 regimen [10].…”
mentioning
confidence: 99%